2015
DOI: 10.1002/aic.15114
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of Pt/C catalyzed aqueous phase glycerol conversion with in situ formed hydrogen

Abstract: Detailed kinetic modeling of Pt/C catalyzed conversion of glycerol to lactic acid, glycols, and alcohols with in situ formed hydrogen is reported. Experimental concentration-time profiles were obtained in a batch slurry reactor at different glycerol concentrations, nitrogen partial pressures, and NaOH concentrations in a temperature range of 130-1608C. Six different kinetic models were evaluated to describe the competing dehydrogenation, hydrogenolysis, dehydration, and CAC cleavage reactions, and discriminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 57 publications
1
35
0
2
Order By: Relevance
“…Both computational and experimental results have shown that dehydrogenation, although thermodynamically unfavorable, is kinetically favorable on metal catalysts . Hydrogenolysis or hydrogenation, on the other hand, seem to follow a different path to that of APH under a H 2 environment.…”
Section: Dual‐function Catalysts For Cthmentioning
confidence: 99%
“…Both computational and experimental results have shown that dehydrogenation, although thermodynamically unfavorable, is kinetically favorable on metal catalysts . Hydrogenolysis or hydrogenation, on the other hand, seem to follow a different path to that of APH under a H 2 environment.…”
Section: Dual‐function Catalysts For Cthmentioning
confidence: 99%
“…Magnetic Pd/Fe 3 O 4 nanocatalysts were designed for selective oxidation of hydroxymethylfurfural to furan dicarboxylic acid (involving oxidation of C=O and C−OH groups), as shown in Figure (e) . Pt (111) surface has also been shown to display bi‐functional properties in polyol hydrogenolysis with in‐situ formed hydrogen (by dehydrogenation) without the need for adding external hydrogen …”
Section: Figurementioning
confidence: 99%
“…Various metal catalysts show promising performances in hydrogenolysis of polyols to 1,2‐PDO, including Pt, Ru, Cu, Ni, among which Ru and Cu catalysts are most extensively studied with promising performances. This is because Ru‐based catalysts show remarkable activity while Cu catalysts often exhibit high selectivity towards 1,2‐PDO.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations